2002
DOI: 10.1521/aeap.14.7.24.23864
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity and HIV Risk Among Adjudicated Alcohol- and Other Drug-Abusing Adolescent Offenders

Abstract: Although impulsivity is likely to be related to HIV risk-particularly in incarcerated substanceabusing youth-this area of research has been understudied. To investigate the relationship between impulsivity and various HIV/AIDS risk behaviors and attitudes, a sample of court-referred and incarcerated culturally diverse inner-city adolescents (males: N = 266; females: N = 111) were divided into high and low impulsive groups based on the Millon Adolescent Clinical Inventory Impulsivity Scale. Findings showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
58
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 38 publications
5
58
0
1
Order By: Relevance
“…Similarly, it is possible that the impulsive nature inherent in individuals with disruptive behavior disorders is influencing the association between these disorders and earlier intercourse. Several studies, for example, have shown associations between the sexual behaviors examined in this study and impulsivity in different samples (Apostolopoulos, Sonmex, & Yu, 2002;Devieux et al, 2002;Hayaki, Anderson, & Stein, 2006;Lejuez et al, 2004). Additionally, personality characteristics such as novelty seeking or a genetic propensity towards addiction may be involved as mechanisms in this relationship (Heath et al, 1997) or familial characteristics in childhood such as education level of mother (Fergusson & Woodward, 2000).…”
Section: Discussionmentioning
confidence: 70%
“…Similarly, it is possible that the impulsive nature inherent in individuals with disruptive behavior disorders is influencing the association between these disorders and earlier intercourse. Several studies, for example, have shown associations between the sexual behaviors examined in this study and impulsivity in different samples (Apostolopoulos, Sonmex, & Yu, 2002;Devieux et al, 2002;Hayaki, Anderson, & Stein, 2006;Lejuez et al, 2004). Additionally, personality characteristics such as novelty seeking or a genetic propensity towards addiction may be involved as mechanisms in this relationship (Heath et al, 1997) or familial characteristics in childhood such as education level of mother (Fergusson & Woodward, 2000).…”
Section: Discussionmentioning
confidence: 70%
“…Motivational enhancement in the current study was not directly focused on altering sexual risk behaviors, per se, so our effect for overall sexual risk was surprising. Heightened levels of sexual risk behavior occur in combination with substance use and intoxication among adolescent detainees (Devieux et al, 2002;Gary et al, 2000;Harwell et al, 1999;Kingree et al, 2002). Future efforts to directly address reducing participation in high-risk sexual behaviors among incarcerated adolescents are definitely warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Out of approximately 2.4 million juvenile arrests each year, more than 203,000 are for offenses related to substance use (Snyder, 2002). As is true for many sexually active populations, heightened levels of sexual risk behavior occur in combination with substance use and intoxication among adolescent detainees (Devieux et al, 2002;Gary et al, 2000;Harwell, Trino, Rudy, Yorkman, & Gollub, 1999;Kingree, Braithwaite, & Woodring, 2002). One study (Castrucci & Martin, 2002) found a strong association between regular substance use and sexual risk (including multiple sex partners, inconsistent condom use, and trading sex for money or drugs) among their sample of incarcerated adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…First, the AM intervention, which is based on an anger management protocol, targeted skills related to improving impulse control and emotional selfmanagement. Impulsivity has been implicated in the risk behavior of juvenile justice youth, including risky sex and drug use [30] . For example, studies with adolescents having conduct and substance use problems showed higher levels of impulsivity compared to community controls [31] .…”
Section: Discussionmentioning
confidence: 99%